2006
DOI: 10.1177/14690446060070010701
|View full text |Cite
|
Sign up to set email alerts
|

Is there an opportunity to reduce urinary catheter-related infections? Exploring variation in catheterisation rates in care homes

Abstract: Birmingham B9 5SSrinary catheterisation in care homes is associated with increased morbidity, hospitalisation and mortality. The authors aimed to determine whether staffing, resident underlying illness or nursing band, or use of other toileting methods were responsible for the wide variation in urinary catheterisation rates found in English care homes. The authors approached randomlyselected registered care homes in three former health districts in England. A questionnaire survey was used to determine the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 6 publications
0
21
0
Order By: Relevance
“…, 1997), poststroke (Bean et al. , 2003), use of long‐term indwelling urethral catheters as a management technique (McNulty et al. , 2006a,b), night‐time sleep and bed mobility (Schnelle et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…, 1997), poststroke (Bean et al. , 2003), use of long‐term indwelling urethral catheters as a management technique (McNulty et al. , 2006a,b), night‐time sleep and bed mobility (Schnelle et al.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies were undertaken in the USA. The number of care homes involved ranged from four to 841 care homes, although one study did not specify (McNulty et al. , 2006a,b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although all staff reported using a sterile pack and almost all reported appropriate hand-washing, 16% of nursing staff, and 17% of care staff reported using multi-use lubricant (from a tube) for catheter insertion ( McNulty et al, 2006b ). The need for sterile single-use lubricant should be made clear in all education about catheter insertion.…”
Section: Insertion Of Urinary Cathetersmentioning
confidence: 98%
“…A US study showed that 23% of 39,282 postoperative patients discharged to nursing homes had urinary catheters; those patients discharged with catheters had a greater risk of rehospitalisation and death (Wald et al, 2008). The wide variation in urinary catheterisation has previously been explored by us (McNulty et al, 2006(McNulty et al, , 2008 and is not due to differences in rates of residents' incontinence or nursing needs). Homes with lower prevalence of catheterisation or no catheters took a more proactive approach to removing inherited catheters, toileting, managing continence, and mobility; these homes often had a different culture of care aimed at maintaining residents' dignity and independence.…”
Section: Strengths and Limitationsmentioning
confidence: 99%